ANALYSIS OF THE SLANG WORD 'KUY' IN EVERYDAY LANGUAGE CONTEXT - Rahmadani, Suci; Nasution, Jamaluddin; Pardede, Widya Karolina Br; Nabilla, Alyah Putri; Pandia, Kesya Klarissya Br (Smart Education, 2025)
Abstract: This study analyzes the use of the slang word “kuy” in the daily language of Indonesian society, particularly among teenagers and young adults. Using a qualitative approach and descriptive-analytical method, data were collected through questionnaires from 107 respondents, in-depth interviews, social media observation, and digital documentation. The findings show that “kuy” originates from the phonological reversal of the word “yuk” in prokem language, which emerged in the 1980s and gained popularity on social media around 2014. Semantically, 89.7% of respondents understand “kuy” as an invitation, but pragmatically, it also serves as a symbol of social closeness and group identity, with 57.9% considering it important to express familiarity among peers. The word is most commonly used to invite someone to do something (52.8%) and appears more frequently in social media communication than in face-to-face interaction. Its usage is moderate, with 85% of respondents using it occasionally, reflecting the younger generation’s ability to code-switch according to the communication context. This study concludes that “kuy” is not only a linguistic expression but also a cultural artifact that reflects the creativity and social dynamics of Indonesia’s urban digital generation. Keywords: slang, kuy, sociolinguistics, prokem language, social media, adolescent identity, language variation, digital communication, Gen Z, Indonesian slang. Abstrak: Studi ini menganalisis penggunaan kata slang